1996
DOI: 10.1111/j.1600-0897.1996.tb00012.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Histocompatibility Antigens in Recurrent Spontaneous Abortion Couples and on Their Reproductive Performances

Abstract: The results suggest that gene(s) disadvantageous for reproduction may exist between the HLA-B and -DR chromosomal region which influences the pregnancy outcome in RSA couples, and that HLA-antigen sharing itself does not influence the outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
1
6
1
Order By: Relevance
“…Therefore, the original hypothesis of a strong HLA compatibility as a cause of RA [26,27] cannot be corroborated with our data [9,28,29].…”
Section: Immune Geneticscontrasting
confidence: 55%
“…Therefore, the original hypothesis of a strong HLA compatibility as a cause of RA [26,27] cannot be corroborated with our data [9,28,29].…”
Section: Immune Geneticscontrasting
confidence: 55%
“…10,16 Some investigators have found increased HLA sharing in all regions of the MHC, 6,10,[17][18][19][20] especially in the HLA-B and HLA-DR loci. [21][22][23][24][25][26][27] Others have found no difference in HLA sharing between couples with recurrent pregnancy loss and fertile controls. 8,28-34 Some investigators have reported an association between spe-cific HLA haplotypes and alleles and an increased risk for pregnancy loss.…”
Section: Parental Shared Human Leukocyte Antigensmentioning
confidence: 99%
“…24,[35][36][37][38][39][40] However, others have found no association between recurrent pregnancy loss and specific HLA types. 26,27,34,41 There are several possible explanations for the confusing and sometimes conflicting data regarding HLA sharing in couples with recurrent pregnancy loss. Studies differ with regard to HLA alleles tested, methods of HLA typing, definitions of recurrent pregnancy loss, the type of controls used, and the heterogeneity of ethnic groups included.…”
Section: Parental Shared Human Leukocyte Antigensmentioning
confidence: 99%
See 2 more Smart Citations